2016
DOI: 10.1186/s13064-016-0073-y
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral migration of oculomotor neurons is regulated by Slit/Robo signaling

Abstract: BackgroundOculomotor neurons develop initially like typical motor neurons, projecting axons out of the ventral midbrain to their ipsilateral targets, the extraocular muscles. However, in all vertebrates, after the oculomotor nerve (nIII) has reached the extraocular muscle primordia, the cell bodies that innervate the superior rectus migrate to join the contralateral nucleus. This motor neuron migration represents a unique strategy to form a contralateral motor projection. Whether migration is guided by diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Lhx1 ( Figure 1N). Different axon guidance-related genes are expressed by oculomotor and spinal cord motor neurons during development (Bjorke et al, 2016;Gutekunst and Gross, 2014;Stark et al, 2015;Wang et al, 2011). To further characterize the in vitro generated oculomotor neurons, we analyzed their mRNA expression of morphological markers that are important for axon guidance.…”
Section: Bona Fide Oculomotor Neurons Can Be Generated From Mescsmentioning
confidence: 99%
“…Lhx1 ( Figure 1N). Different axon guidance-related genes are expressed by oculomotor and spinal cord motor neurons during development (Bjorke et al, 2016;Gutekunst and Gross, 2014;Stark et al, 2015;Wang et al, 2011). To further characterize the in vitro generated oculomotor neurons, we analyzed their mRNA expression of morphological markers that are important for axon guidance.…”
Section: Bona Fide Oculomotor Neurons Can Be Generated From Mescsmentioning
confidence: 99%
“…Thus the ROBO1 gene may be one of the potential causative genes for PSIS and CPHD. Bjorke et al (20) showed that Slit signaling is necessary to inhibit the initiation of oculomotor neuron development. Oculomotor axons at the midline crossing are characterized by an axon-like process that forms from the cell body as a secondary axon.…”
Section: Discussionmentioning
confidence: 99%
“…It is habitual that neurons send their axonal process toward contralateral side of the brain but not that neurons project ipsilaterally and afterwards they migrate their soma to the contralateral side. The migration is independent of Netrin1 (present in the floor and basal plates) and dependent of the receptor family Robo and their ligand family Slits (Bjorke et al, ). This phenomenon has been described in several vertebrate species (Puelles and Privat, ; Puelles, ; Naujoks‐Manteuffel et al, ).…”
Section: Developmentmentioning
confidence: 99%